Evaluation of remission definitions for systemic lupus erythematosus: a prospective cohort study. (October 2019) - Golder, Vera; Kandane-Rathnayake, Rangi; Huq, Molla; Louthrenoo, Worawit; Luo, Shue Fen; Wu, Yeong-Jian Jan; Lateef, Aisha; Sockalingam, Sargunan; Navarra, Sandra V; Zamora, Leonid; Hamijoyo, Laniyati; Katsumata, Yasuhiro; et al.
Summary: Background: Validated outcome measures are needed from which to derive treatment strategies for systemic lupus erythematosus (SLE). However, no definition of remission for SLE has been widely adopted. The Definitions of Remission in Systemic Lupus Erythematosus (DORIS) group has proposed a framework with multiple potential definitions of remission. In this study, we aimed to assess the attainability and effect on disease outcomes of the DORIS definitions of remission, compared with the lupus low disease activity state (LLDAS), in patients with SLE. Methods: In this prospective cohort study, we enrolled patients with SLE from 13 international centres that are part of the Asia Pacific Lupus Collaboration. Eligible patients were older than 18 years and fulfilled one of two classification criteria for SLE (1997 American College of Rheumatology criteria or the 2012 Systemic Lupus International Collaborating Clinics criteria). Visits were according to clinical need, with a minimum frequency of one visit per 6 months. We assessed attainment of remission on the basis of the eight DORIS definitions of remission, which varied in terms of serological activity, glucocorticoid use, and use of immunosuppresive agents; attainment of LLDAS; and disease flares at each visit. Irreversible organ damage accrual was recorded annually. Our primary aim was to assess exposure of patients to each of the remission definitions or LLDAS, and the respective association of these states with accrual of irreversible organ damage as the primary outcome measure. Occurrence of disease flares was the key secondary outcome. We used time-dependent Cox proportional hazards models and generalised linear models to assess DORIS definitions of remission and LLDAS in terms of their association with damage accrual and disease flares. Findings: Between May 1, 2013, and Dec 31, 2016, 1707 patients with SLE were recruited and followed for a mean of 2·2 years (SD 0·9), totalling 12 689 visits. Remission, depending on DORIS definition, was achieved in 581 (4·6%) to 4546 (35·8%) of 12 689 visits. Spending 50% or more of observed time in any remission state was associated with a significant reduction in damage accrual, except for the two most stringent remission definitions, for which the frequency of attainment was lowest. Remission definitions disallowing serological activity were associated with the greatest reductions in disease flares. LLDAS was more attainable than any remission definition and was associated with a similar magnitude of protection from damage accrual and disease flares. Sustained remission and LLDAS were associated with a wider spread of effect sizes for reduction in risk of damage. By analysing patients who met the definition for LLDAS but not remission, we found that LLDAS was significantly associated with reduction in damage accrual, independent of all definitions of remission, except the least stringent. Interpretation: Attainment of remission was associated with significant reductions in damage accrual and disease flares. LLDAS was more achievable than remission based on the DORIS criteria, but was similarly protective. Remission definitions with less stringency might be insufficiently distinct from LLDAS to substantially affect outcome measures, and further studies are needed to distinguish the protective effects of the various remission definitions. Funding: UCB, GlaxoSmithKline, Janssen, Bristol-Myers Squibb, and AstraZeneca.